Does seeing it make a difference? The self-reported deterrent impact of random breath testing. (February 2021) - Freeman, James; Parkes, Alexander; Truelove, Verity; Lewis, Naomi; Davey, Jeremy D.
Highlights: A sizeable proportion (25%) acknowledged drink driving. Motorists were regularly exposed to RBT operations. Motorists observed RBT operations more often than were tested. Motorists calculated that they needed to be tested more often. Higher exposure to RBT operations reduced the risk of re-offending. Abstract: Introduction: Random Breath Testing (RBT) remains a primary method to both deter and apprehend drink drivers, yet a large proportion of road fatalities continue to be caused by the offense. Outstanding questions remain regarding how much exposure to RBT operations is needed to influence deterrence-based perceptions and subsequent offending. Method: Given this, licensed motorists ( N  = 961) in Queensland were recruited to complete a questionnaire either in the community ( N  = 741) or on the side of the road after just being breath tested ( N  = 243). Survey items measured different types of exposure to RBT operations (e.g., "seen" vs. "being tested") and subsequent perceptions of apprehension as well as self-reported drink driving behaviors. Results: The key findings that emerged were: motorists were regularly exposed to RBT operations (both viewing and being tested), such exposure was not significantly correlated with perceptions of apprehension certainty, and a sizable proportion reported engaging in drink driving behaviors (e.g., approx. 25%), although roadside participants naturally reported a lower percentage of offending behaviors. Importantly, it was revealed that current "observations" of RBT was sufficient, but not actual levels of active testing (which needed to be doubled). Nevertheless, higher levels of exposure to RBT operations was found to be predictive of a lack of intention to drink and drive again in the future. Conclusions: This paper suggests that mere exposure to enforcement may not create the intended rule compliance, and that the frequency of exposure is also essential for the roadside.